Calcipotriol Inhibits NLRP3 Signal Through YAP1 Activation to Alleviate Cholestatic Liver Injury and Fibrosis - Xiaopeng Wang; Guiyang Wang; Junwen Qu; Zhiqing Yuan; Ruogu Pan; Kewei Li (Frontiers Media S.A., 2020)
Cholestasis is common in multiple clinical circumstances. The NOD-like receptor protein 3 (NLRP3) inflammasome pathway has been demonstrated to play an important role in liver injury and fibrosis induced by cholestasis. We previously proved that MCC950, a selective NLRP3 inhibitor, alleviates liver fibrosis and injury in experimental liver cholestasis induced by bile-duct ligation (BDL) in mice. Herein, we investigate the role of calcipotriol, a potent vitamin D receptor agonist, in experimental liver cholestasis, test its therapeutic efficacy, and explore its potential protective mechanism. C57BL/6 mice were made to undergo BDL or fed the 0.1% 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet to establish two classic cholestatic models. Calcipotriol was administered intraperitoneally to these mice daily. Serum makers of liver damage and integrity, liver histological changes, levels of liver pro-fibrotic markers, bile acid synthetases and transporters were measured in vivo. The underlying mechanism by which calcipotriol alleviates cholestatic liver injury and fibrosis was further investigated. The results of the current study demonstrated that calcipotriol supplement significantly alleviate cholestatic liver injury and fibrosis. Moreover, calcipotriol supplement markedly inhibited NLRP3 inflammasome pathway activation to alleviate liver injury and fibrosis in vivo and inhibit hepatic stellate cell (HSC) activation in vitro. In addition, VDR agonist calcipotriol exert inhibitory effect on NLRP3 inflammasome activation through activating yes-associated protein 1 (YAP1). In conclusion, our findings proved that calcipotriol suppressed the NLRP3 signal by activating YAP1 to alleviate liver injury and retard fibrogenesis in cholestasis.